Optimalisasi Peran Generasi Z sebagai Khatib Muda dalam Membangun Peradaban Umat di Era Digital - Ma’zumi, Ma’zumi; Suja’i, Suja’i; Najmudin, Najmudin (JPM: Jurnal Pengabdian Masyarakat, 2026)
The Friday sermon (khutbah Jum‘ah) faces challenges in engaging Generation Z, as sermons often seem detached from their realities. Yet, the khutbah has strategic potential as a tool for spiritual and social development within the mosque community. This community service program aims to strengthen the capacity of young preachers (khatib muda) from Generation Z through contextual sermon training that is relevant to the challenges of the digital era, while utilizing the mosque as a center for community empowerment. The program was carried out in collaboration with the Campus Mosque of Sultan Ageng Tirtayasa University, a strategic partner that provided participants, facilities, and support for implementing post-sermon action programs. The project used a Participatory Action Research (PAR) approach, emphasizing that participants actively engaged in every program stage, including: (1) intensive training for young preachers on sermon substance and the mosque’s social role; (2) sermon practice and direct mentoring; (3) observing and evaluating sermon delivery; and (4) conducting post-sermon social and religious action programs. Data were collected through participatory observation, interviews, and documentation, and analyzed descriptively and qualitatively using triangulation techniques. The activities showed a significant improvement in participants’ rhetorical competence, sermon content, and social sensitivity. Approximately 85% of participants successfully developed sermon manuscripts with contextual themes, and 78% delivered sermons that engaged the audience. Post-sermon programs such as Green Dakwah, Masjid Talk Gen Z, and digital literacy training successfully increased youth congregation participation and strengthened the mosque’s role as a collaborative community space. The training of Generation Z preachers proved effective in reinforcing the khutbah's role as a holistic instrument for community development.